Ultrasensitive immuno-detection using viral nanoparticles with modular assembly using genetically-directed biotinylation - Litvinov, Julia (2014)
We report a novel, modular approach to immuno-detection based on antibody recognition and PCR read-out that employs antibody-conjugated bacteriophage, easily-manipulated nonpathogenic viruses, as affinity agents. Our platform employs phage genetically tagged for in vivo biotinylation during phage maturation that can easily be linked, through avidin, to any biotinylatable affinity agent, including full-length antibodies, peptides, lectins or aptamers. The presence of analyte is reported with high sensitivity through real-time PCR. This approach avoids the need to clone antibody-encoding DNA fragments, allows the use of full-length, high affinity antibodies and, by having DNA reporters naturally encapsulated inside the bacteriophage, greatly reduces nonspecific binding of DNA. We validate the efficacy of this new approach through the detection of VEGF (Vascular Endothelial Growth Factor), a known angiogenic cancer biomarker protein, at attomolar concentrations in bronchoalveolar lavage (BAL) fluid.